Faricimab: Transforming the Future of Macular Diseases Treatment - A Comprehensive Review of Clinical Studies - Panos GD; Lakshmanan A; Dadoukis P; Ripa M; Motta L; Amoaku WM (Dove Medical Press, 2023)
Georgios D Panos,1,2 Arun Lakshmanan,1 Panagiotis Dadoukis,3 Matteo Ripa,4 Lorenzo Motta,4 Winfried M Amoaku1,2 1Department of Ophthalmology, Queen's Medical Centre, Nottingham University Hospitals, Nottingham, UK; 2Division of Ophthalmology and Visual Sciences, Faculty of Medicine & Health Sciences, School of Medicine, University of Nottingham, Nottingham, UK; 3Eye Treatment Centre, Whipps Cross University Hospital, Barts Health NHS Trust, London, UK; 4Department of Ophthalmology, William Harvey Hospital, East Kent Hospitals University NHS Foundation Trust, Kent, UKCorrespondence: Georgios D Panos, Department of Ophthalmology, Queen's Medical Centre, Derby Road, Lenton, Nottingham, NG7 2UH, UK, Tel +44 115 924 9924, Email gdpanos@gmail.com Lorenzo Motta, Department of Ophthalmology, William Harvey Hospital, Kennington Road, Willesborough, Ashford, Kent, TN24 0LZ, UK, Tel +44 1233 633331, Email lorenzo.motta@nhs.netAbstract: Degenerative eye conditions such as age-related macular degeneration (AMD), diabetic retinopathy, and retinal vein occlusion are major contributors to significant vision loss in developed nations. The primary therapeutic approach for managing complications linked to these diseases involves the intravitreal delivery of anti-vascular endothelial growth factor (VEGF) treatments. Faricimab is a novel, humanised, bispecific antibody that simultaneously binds all VEGF-A isoforms and Angiopoietin-2, which has been approved by regulatory agencies, such as the US Food and Drug Administration (FDA), the UK Medicines and Healthcare products Regulatory Agency (MHRA) and the European Medicines Agency (EMA), for the treatment of neovascular AMD and diabetic macular oedema (DMO). Intravitreal faricimab holds the promise of reducing the treatment burden for patients with these conditions by achieving comparable or superior therapeutic outcomes with fewer clinic visits. The scope of faricimab's application includes addressing complex macular conditions such as DMO. This review intends to elucidate the distinctive pharmacological characteristics of faricimab and provide an overview of the key clinical trials and real-world studies that assess its effectiveness and safety in treating degenerative macular diseases.Keywords: degenerative macular disorders, faricimab, anti-VEGF, efficacy, safety, intravitreal treatment, age-related macular degeneration, diabetic macular oedema, retinal vein occlusion, diabetic retinopathy